Efek Pemberian Pupuk Hayati Mikoriza dan Kosentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt.) - Muyasir Muyasir; Nurhayati Nurhayati; Rika Husna (Jurnal Agrotek Lestari, 2022)
Sweet corn (Zea mays saccharata Sturt.) is one of the world's most important food crops besides wheat and rice, because corn is the second source of carbohydrates after rice. One of the efforts to increase national corn production is through fertilization. The continuous use of inorganic fertilizers such as NPK can cause the balance of nutrients in the soil to be disturbed, so that growth is disrupted and productivity decreases. To overcome these problems and constraints, one of the efforts made is the use of biological fertilizers, one of which is mycorrhizal biological fertilizer and liquid organic fertilizer. This research aimed to determine the effect of the dosage of mycorrhizae biological fertilizer and the concentration of liquid organic fertilizer and to determine whether there is an interaction between the treatment dosage of mycorrhizal biological fertilizer and the concentration of liquid organic fertilizer on the growth and yield of sweet corn. This research was carried out at the Experimental Garden of the Faculty of Agriculture of Universitas Syiah Kuala, Darussalam, Banda Aceh, which took place from March to May 2021. This research used a 4x3 factorial randomized block design consisting of 2 treatments and 3 replications. The results showed that the dosage of mycorrhizal biofertilizer 15 g/plant was better for the growth and yield of sweet corn, the better growth and yield of sweet corn was found in the concentration of liquid organic fertilizer 45 ml/L of water, there was no significant interaction between the dosage of biofertilizer mycorrhizae and concentration of liquid organic fertilizer on all parameters.